EFFECTS OF MUTATIONS OF MYOSTATIN (MSTN) GENE IN BREEDS OF SHEEP IN NIGERIA - Zakka, T. E.; Mancha, Y. P.; Bello, K. M.; Garba, A. M.; Luka, P. N. (Nigerian Journal of Agriculture and Agricultural Technology, 2024)
Growth Differentiation Factor 8 (GDF8), also known as myostatin, is a member of the Transforming Growth Factor β (TGFβ) superfamily. It has been reported to act as a negative extracellular regulator and a significant negative regulator of skeletal muscle mass, muscle growth, and development. This research was carried out to identify the effects of molecular genetic variation of the myostatin (MSTN) gene in breeds of sheep in Nigeria, using, in silico tools. A total of eight myostatin (MSTN) nucleotide sequences were retrieved from NCBI (National Centre for Biotechnology Information) website (www.ncbi.nlm.nih.gov) it was aligned, translated, and compared using Clustal W from MEGA to find genetic distances and evolutionary relationships. BLAST tool was used to align and identify the mutations of the sequences considered. The variation in sequence length base pairs (bp) were 511 and 580 bp. Functional analysis of missense mutations using SIFT identified twenty-one (21) amino acids substitutions in the myostatin (MSTN) gene sequences. (18 were tolerant or beneficial while 3 were deleterious or harmful). There were 7 Essential to Essential substitutions, 5 Essential to Non-Essential substitutions, 4 Non-Essential to Non-Essential substitutions, 5 Non-Essential to Essential substitutions. The beneficial mutations were more prevalent than the harmful mutations. There should be Implementation of selective breeding strategies to propagate the beneficial mutations identified, enhancing muscle growth and meat yield in breeds of sheep in Nigeria.